STRATEGI PENGEMBANGAN AGROINDUSTRI JAMU DI JAWA TIMUR [Development Strategy of Herbal Medicine Agroindustry in East Java] - Nurmayasari Nurmayasari; Asfan Asfan; Mohammad Fuad Fauzul Mu'tamar (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2018)
Herbal medicine agro-industry has experienced ups and downs in its development, the movement back to nature makes herbal medicine agro-industry has developed quite rapidly. This study aimed to determine the structure and factors that influence and determine the strategy of herbal medicine agro-industry development in East Java. The method used was OLS (Ordinary Least Square) and Backward method using secondary data, as well as the concentration ratio and PCM (Price Cost Margin) proxy. The results showed that the industrial market structure was tight oligopoly with an average concentration ratio of 76.22%. Influencing factors were market concentration, barriers to market entry, a value of efficiency and number of companies, while the strategy developed was to streamline raw material costs by implementing multiple supplier policies